Shakedown analysis of composite steel-concrete frame systems with plastic and brittle elements under seismic action = Przystosowanie zespolonych stalowo-betonowych układów ramowych zawierających plastyczne i kruche elementy przy obciążeniach sejsmicznych - Alawdin, Piotr; Bulanov, George (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper the earthquake analysis of composite steel-concrete frames is performed by finding solution of the optimization problem of shakedown analysis, which takes into account the nonlinear properties of materials. The constructions are equipped with systems bearing structures of various elastic-plastic and brittle elements absorbing energy of seismic actions.
Keywords: limit analysis; shakedown analysis; composite frames; steel-concrete frames; seismic-protected system; nośność graniczna; ramy zespolone; ramy stalowo-betonowe; układ nośny; elementy sprężysto-plastyczne; ochrona sejsmiczna